2014
DOI: 10.1073/pnas.1304212111
|View full text |Cite
|
Sign up to set email alerts
|

Requirements and limits for life in the context of exoplanets

Abstract: The requirements for life on Earth, its elemental composition, and its environmental limits provide a way to assess the habitability of exoplanets. Temperature is key both because of its influence on liquid water and because it can be directly estimated from orbital and climate models of exoplanetary systems. Life can grow and reproduce at temperatures as low as −15°C, and as high as 122°C. Studies of life in extreme deserts show that on a dry world, even a small amount of rain, fog, snow, and even atmospheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 72 publications
1
79
0
Order By: Relevance
“…We also observed differential light transmission across wavelengths for all rocks, with higher transmission in the infrared, which is in agreement with red wavelengths penetrating deeper than blue wavelengths (McKay, ). Spectral tuning of photosystem II has been reported in Cyanobacteria (Croce and van Amerongen, ) and experimentally demonstrated with Synechococcus variants in microbial mats from hot springs (Becraft et al ., ), suggesting a potential adaptation to low quantum flux densities for endolithic Cyanobacteria .…”
Section: Discussionsupporting
confidence: 86%
“…We also observed differential light transmission across wavelengths for all rocks, with higher transmission in the infrared, which is in agreement with red wavelengths penetrating deeper than blue wavelengths (McKay, ). Spectral tuning of photosystem II has been reported in Cyanobacteria (Croce and van Amerongen, ) and experimentally demonstrated with Synechococcus variants in microbial mats from hot springs (Becraft et al ., ), suggesting a potential adaptation to low quantum flux densities for endolithic Cyanobacteria .…”
Section: Discussionsupporting
confidence: 86%
“…Finally, we detect active silica encrustment/fossilization of cells but also abiotic biomorphs of varied chemistry in samples where there is no life. Our work has implications to circumscribe planetary habitability (11,12), raising warnings for the interpretation of morphological biosignatures on Earth and beyond.…”
mentioning
confidence: 89%
“…Our ideas concerning processes on other heavenly bodies are constantly being challenged and adjusted. Grotzinger et al (2014) recently reported on a relatively young, likely habitable environment on Mars that could have supported an ecosystem based on chemolithoautotrophy, and McKay (2014) reported that the surface of Mars has adequate carbon to support life. Levin and Straat (2014) actually contend that missions to Mars have found proof of living microorganisms on that planet.…”
Section: Calls For a New Definitionmentioning
confidence: 99%